No-go limitations on UV completions of the neutrino option - Brivio, Ilaria; Talbert, Jim; Trott, Michael (Physical review, 2021)
We discuss the possible origin of the Majorana mass scale(s) required for the “neutrino option” where the electroweak scale is generated simultaneously with light neutrino masses in a type-I seesaw model by common dimension four interactions. We establish no-go constraints on the perturbative generation of the Majorana masses required due to global symmetries of the seesaw Lagrangian.
Gesehen am 02.04.2022